Publication Rates of Abstracts Presented at the Urological Society of Australia and New Zealand Annual Scientific Meeting Keith Kirkland and Villis Marshall Session: A Decade‐Long Review - Fung, Cheryl; Vo, Lequang T.; Armany, David; Indrajit, Balasubramaniam; Bariol, Simon V.; Hossack, Tania; Baskaranathan, Sriskanthan; Ende, David; Woo, Henry H. (ANZ journal of surgery, 2025)
ABSTRACT Background The publication rate of s at scientific meetings reflects research quality and impact, highlighting its dissemination within the academic and clinical communities. The Keith Kirkland and Villis Marshall (KK/VM) Session, held annually at the Urological Society of Australia and New Zealand (USANZ) Annual Scientific Meeting (ASM), features top s from Urology SET Trainees. While the Board selects s for presentation, their publication rates remain unclear. This study aims to determine the full‐article publication rate of s presented at the KK/VM session from 2012 to 2022. Methods The published Scientific Program of the USANZ ASM from 2012 to 2022 was retrospectively reviewed. All s accepted for presentation at the KK/VM sessions were identified from the named plenary session. These s were tracked for their subsequent publication status. Successful publication was defined as those identified in a search on PubMed using the title and author name. Analysis of the successful publication was conducted. Results One hundred and thirty‐five s were identified. 51.85% were subsequently published in peer‐reviewed journals, most commonly in the BJU International (27.14%), The Journal of Urology (18.57%), and the ANZ Journal of Surgery (8.57%). The average time to publication was 14.58 months. The proportion of prospective studies among published (51.4%) and unpublished (52.3%) s was similar. Conclusion The USANZ ASM KK/VM session achieved a 51.85% full‐article publication rate from 2012 to 2022, surpassing the broader USANZ ASM rate. This underscores the high quality of research by Urology SET Trainees. Targeted support could boost publication rates, improving urology research dissemination.